A new species of the genus Rambutanura Deharveng, 1988 from southern Vietnam (Collembola, Neanuridae) - Babenko, Anatoly; Antipova, Maria (Zootaxa, 2024)
Rambutanura oblita sp. nov. from the southern part of Vietnam is described and illustrated. It differs from all previously known species of the genus by the presence of only seven tubercles on the head (tubercle Cl undeveloped, vs present in all other known congeners), and of elongated digitate tubercles only on three last abdominal segments. In all other species such prolonged, finger-like tubercles are either present also on the head and thorax or completely undeveloped.